Representaciones sociales de la leucemia en padres de niños diagnosticados con esta enfermedad del Instituto Nacional de Enfermedades Neoplásicas - Colmenares Morelli, María Paula (2016)
In this study, representations of leukemia in parents of children diagnosed with this disease by their gender, level of education and place of origin, in terms of identity, causes, consequences, development and possible cure are explored. For this, 12 parents of hospitalized children at Instituto Nacional de Enfermedades Neoplásicas that presented this diagnosis were interviewed. The results showed a wide variety in terms of how this disease is conceptualized, considering that parents with a higher level of education link it more closely with biological aspects than environmental aspects, which is mostly referred to by parents with a lower level of instruction. Also, variations between the ability to portray a future situation are illustrated, taking into account the implications and limitations that the disease itself entails. Besides, sense of guilt is found in both parents, with a higher intensity in mothers. Likewise, the lack of knowledge about conventional treatment in parents from the Peruvian jungle is shown, as does the tendency to seek the cause of the disease in cultural elements.